(untitled) (Global Journals of Research in Engineering, 2017)
This prospective work aims to evaluate the weldability of thin sheets of NiTi shape memory alloy by friction stir welding process. The phase transformation temperature was determined by ERT, the mechanical properties were evaluated by Vickers microhardness and tensile test. The fracture surface was investigated by SEM. The welded joints remained in the austenitc state after welding, achieved ultimate tensile strength of 700 MPa and 13% strain the main fracture mode was ductile.